Author in The Monuments of Late Antique Christian Hagiography - Alexandra S. Balakhovskaya (Studia Litterarum)
The paper deals with the problem of authorship in the monuments of Late Antique hagiography, namely “The Life of St. Anthony the Great” written by Athanasius of Alexandria, and “The Lausiac History” by Palladius of Helenopolis. In the “Life” of Anthony the Great, the formation of the author’s self-awareness was influenced by such factors as the ancient rhetorical tradition and the late antique Christian ascetic theory and practice of humility. Athanasius, having been aware of the greatness of his hero, claims that he does not have the opportunity to talk about all the details of his life and recommends contacting other people who knew him, thereby limiting his authorship to external authority. Palladius of Helenopolis, similarly being in the context of the rhetoric of humility, additionally models his authorship according to the biblical model. Following the patterns of the authors of biblical books, he identifies himself as a preacher of the truth and uses simple language. Thus, for him, the tradition of biblical authorship serves as an external authority. So, both Athanasius of Alexandria and Palladius of Helenopolis comprehend their authorship within the framework of the tradition, humiliating themselves.